2015
DOI: 10.1094/pdis-04-14-0374-re
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Alternaria alternata from Citrus to Boscalid and Polymorphism in Iron-Sulfur and in Anchored Membrane Subunits of Succinate Dehydrogenase

Abstract: Vega, B., and Dewdney, M. M. 2015. Sensitivity of Alternaria alternata from citrus to boscalid and polymorphism in iron-sulfur and in anchored membrane subunits of succinate dehydrogenase. Plant Dis. 99:231-239.Boscalid, a succinate dehydrogenase inhibitor (SDHI), was registered in 2011 to control Alternaria brown spot (ABS) of citrus, caused by Alternaria alternata. In this study, the effect of boscalid on mycelial growth, conidial germination, and resazurin reduction was established in a subset of 16 sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(117 reference statements)
2
8
0
4
Order By: Relevance
“…SDHI-resistance has become a serious problem in agriculture, leading to a decrease of control efficacy [20,26,27]. Several studies have shown that double mutation in SDH gene further reduces susceptibility to SDHI than single point mutation, leading to a reduction of control efficacy of SDHI fungicides [6,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…SDHI-resistance has become a serious problem in agriculture, leading to a decrease of control efficacy [20,26,27]. Several studies have shown that double mutation in SDH gene further reduces susceptibility to SDHI than single point mutation, leading to a reduction of control efficacy of SDHI fungicides [6,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism in sdhB , sdhC and sdhD gene sequences found in our study resembled the polymorphism found in A. alternata . In A. alternata isolates resistant to boscalid, 21 mutations were identified in the genes encoding fungicide‐targeted subunit proteins of SDH; however, no mutations were found in the highly conserved H277 in SDHB, H134 in SDHC and H133 in SDHD, typically observed in boscalid‐resistant isolates …”
Section: Discussionmentioning
confidence: 99%
“…In A. alternata isolates resistant to boscalid, 21 mutations were identified in the genes encoding fungicide-targeted subunit proteins of SDH; however, no mutations were found in the highly conserved H277 in SDHB, H134 in SDHC and H133 in SDHD, typically observed in boscalid-resistant isolates. 43 In laboratory-induced SDHI-resistant mutants of Mycosphaerella graminicola (Fuckel) J. Schröt. in Cohn, the causal agent of Septoria leaf blotch on wheat, 27 amino acid substitutions occurred at different positions in the three subunits SDHB, SDHC and SDHD, and it was indicated that resistance might be conditioned by sequence variation in multiple subunits of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous reports that germination rates and hyphal development are decreased by this fungicide. Both germination rate and hyphal growth of Alternaria alternata and Penicillium digitatum were inhibited by boscalid treatment (Vega and Dewdney, 2015;Xu et al, 2020). Also, it was reported that the germination rate of Puccinia striiformis causing stripe rust in wheat (Kang et al, 2019) or Colletotrichum acutatum causing anthracnose in chili (Gao et al, 2017), was decreased by pyraclostrobin.…”
Section: Discussionmentioning
confidence: 98%